Comprehensive Characterization of Microbial Community in the Female Genital Tract of Reproductive-Aged Women in China - Sun, Ningxia; Ding, Haixia; Yu, Hongjing; Ji, Yixuan; Xifang, Xiuyue; Pang, Wenjuan; Wang, Xiang; Zhang, Qing; Li, Wen (Frontiers in Cellular and Infection Microbiology, 2021)
The microbiota in the human body play critical roles in many physiological and pathological processes. However, the diversity and dynamics of the female genital tract (FGT) microbiota have not been fully unveiled. In this study, we characterized the microbiome variations in reproductive-aged Chinese women, and we revealed that the cervicovaginal microbiota were dominated by Lactobacillus. Overall, the composition of microbiota in the uterine cavity was more diverse than that in the vagina and cervix. A positive correlation between Lactobacillus iners and Lactobacillus crispatus was observed in both the vagina and the cervix, suggesting that these two species might have a symbiotic relationship in the cervicovaginal microbiota. Moreover, we, for the first time, stratified the reproductive-aged Chinese women into subgroups, based on their microbiome profiles. Furthermore, we identified the bacteria whose abundance changed in the uterine cavity of infertile patients when compared with healthy controls, such as L. iners and L. crispatus. Functionally, the metabolism-related pathways, neurotrophin signaling pathway, and adipocytokine signaling pathway were predominantly dysregulated in the uterine cavity of infertile patients. In conclusion, we characterized a comprehensive microbial landscape in FGT, as well as their functional roles in female infertility of the Chinese population.